Pengaruh Model Pembelajaran Blended Learning dalam Situasi New Normal Covid-19 - Junianti, Rina (Lembaga Bale Literasi, 2023)
This research aims to determine the effect of the Blended Learning Model on Learning Outcomes in the New Normal Covid-19 Situation in Class VII Indonesian Language Subjects at MTs NW Sikur for the 2021/2022 Academic Year. The type of research used is Quasi Experimental. The population of this research is all class VII students at MTs NW Sikur for the 2021/2022 academic year. This research is population research because all members of the population in this study are the sample. Where class VII B is the experimental class while VII A is the control class. The research design used was Nonequivalent Control Group Design. The data collection technique used is a test. The data analysis used was the Polled Variance t-test analysis. The research results showed that the average learning outcome score for the experimental class was 71.2 and the control class was 69.4. To test the normality of the experimental class data, it was obtained that X2count = 4.4521 with X2table = 11.07, because X2count < Meanwhile, the control class data normality test produced X2count = 2.743 with X2table = 11.07, because X2count < X2table, the data was normally distributed. The results of the hypothesis test show that t_count>t_table is 3.913 > 2.942, which means H_0 is rejected and H_is accepted. So it can be concluded that